2017
DOI: 10.3389/fpsyg.2017.00900
|View full text |Cite
|
Sign up to set email alerts
|

The (Biological or Cultural) Essence of Essentialism: Implications for Policy Support among Dominant and Subordinated Groups

Abstract: Most research links (racial) essentialism to negative intergroup outcomes. We propose that this conclusion reflects both a narrow conceptual focus on biological/genetic essence and a narrow research focus from the perspective of racially dominant groups. We distinguished between beliefs in biological and cultural essences, and we investigated the implications of this distinction for support of social justice policies (e.g., affirmative action) among people with dominant (White) and subordinated (e.g., Black, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Ideas about human genetic variation have been and will continue to be important to policy debates about racial inequality (Byrd & Ray, 2015). Belief in genetic essentialism is still predictive of opposition to racially ameliorative policies in White (Byrd & Ray, 2015) and non-White adults in the United States (Soylu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideas about human genetic variation have been and will continue to be important to policy debates about racial inequality (Byrd & Ray, 2015). Belief in genetic essentialism is still predictive of opposition to racially ameliorative policies in White (Byrd & Ray, 2015) and non-White adults in the United States (Soylu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…analogical transfer, genetic essentialism, genetics education, racial prejudice, social cognition 1 | INTRODUCTION Throughout history, the science of genetics has been used to justify policies that helped one race by harming another (Jackson & Depew, 2017). Even today the belief that races are genetically dissimilar is used to justify interethnic hostility (Kimel, Huesmann, Kunst, & Halperin, 2016), prejudice (Dar-Nimrod & Heine, 2011), segregative behavior (Williams & Eberhardt, 2008), and discriminatory policies (Soylu, Estrada-Villalta, & Adams, 2017). Evidence suggests that the biology curriculum plays a role in the perpetuation of this problem (Donovan, 2015b).…”
mentioning
confidence: 99%
“…The accuracy of the testing results has come into question (Park et al 2019;Nelson et al 2018;Krimsky and Johnston 2017;Saey 2018;Royal et al 2010;Agro and Denne 2019;Duster 2016) and numerous concerns have been raised around data collection, control, use and access (Park et al 2019;Zwart, 2009;Nelson et al 2018;Wagner 2010;Roche and Annas 2006;Fullwiley 2008;Phillips 2016;Duster 2016). Further, it has been suggested that in social contexts DNA ancestry testing could lead to a rise in the strengthening of scientifically inaccurate notions of racial difference (Caulfield 2018;Phelan et al 2014;TallBear 2014;Chou 2017), which research has shown can have detrimental social implications (Byrd and Ray 2015;Outram et al 2018;Tadmor et al 2013;Soylu Yalcinkaya, Estrada-Villalta, and Adams 2017;Duster 2016). Indeed, the idea of a biological or genetic categorization of race has been dismissed from a range of perspectives (Caulfield et al 2009;Nelson et al 2018;National Institute of Health 2007;Smedley and Smedley 2005;Kahn et al 2018;Duster 2016), and in turn, "race" is more commonly posited as a social construct (Nelson et al 2018;Kahn et al 2018;Machery and Faucher 2005;Onwuachi-Willig 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these beliefs make genetic essentialists prone to the naturalistic fallacy-that racial disparities need not be eliminated because they are an immutable result of human genetics (Lynch, Morandini, Dar-Nimrod, & Griffiths, 2018). Unsurprisingly, then, belief in genetic essentialism predicts opposition to racially ameliorative policies in White (Byrd & Ray, 2015) and non-White adults in the United States (Soylu Yalcinkaya, Estrada-Villalta, & Adams, 2017). This is troubling, given that estimates suggest that 20% of non-Black US citizens believe in genetic essentialism (Morning, Brückner, & Nelson, 2019).…”
Section: Introductionmentioning
confidence: 99%